Inhalation and dermal exposure to toluene among printing workers in a plastic bag factory. Issue 1 (9th November 2018) - Phanprasit, Wantanee; Songpek, Kanchanok; Boonyayothin, Vorakamol; Sujirarat, Dusit
Abstract : Purpose: The purpose of this paper is to explore inhalation levels and dermal exposure to toluene among printing workers who wore no personal protective equipment; it is conducted in a plastic bag factory. Using a charcoal cloth pad (CCP) as a dermal sampler to assess skin permeation of liquid toluene is also investigated. Design/methodology/approach: In total, 27 stationary air samples as well as urine and dermal samples were collected over 9 days from 11 printing workers. Six pieces of CCP were wrapped on each of the workers' fingers for the dermal sample collection. Air samples were collected and analyzed according to NIOSH No. 1501, and 65 post-shift urine samples were collected and analyzed using gas chromatography equipped with headspace sampler (GC-HS/FID). Multiple linear regression was employed to analyze the association between the studied variables. Findings: The mean (SD) urinary toluene (UTol) level was 13.42 (9.72) ug/L. Toluene on the CCP (TolCCP) was a meaningful predictor for UTol ( p -value=0.027) with r and r 2 values of 0.441 and 0.195, respectively. The r and r 2 of the model using the toluene time-weighted average concentrations in air were 0.739 and 0.546, respectively. The absorbed dose of toluene determined from the TolCCP ranged from 1.05 to 91.94 mg, accounting for 12.3 percent of the threshold limit value (TLV). Originality/value: Dermal exposure was insignificant when workers wore respirators, but when not, dermal absorption could contribute to the overall uptake and exposure above the TLV. Appropriate gloves should be assigned to the workers to reduce dermal exposure to toluene.